STUDY ON THE EFFECT OF OBLIQUE IMPACT ANGLE ON THE FAILURE CHARACTERISTICS OF ALUMINUM ALLOY SHEET - HU Jing; Lü YuHan (Jixie qiangdu)
In order to study the failure mechanism of 6061-T651 aluminum alloy sheet under oblique impact, the impact experiments of a hemispherical projectile slanting into a single aluminum alloy sheet at different impact angles（0°, 15°, 30°, 45°） were carried out with a first-stage light gas gun, and the ballistic limit velocity and damage characteristics of the target plate were obtained. The results show that when the size and shape of projectile and target are the same, the ballistic limit of target decreases first and then increases with the increase of impact angle. When the impact angle is 15°, the ballistic limit of aluminum alloy target is the lowest, and the failure mode of target gradually transits from petal cracking to tensile tearing failure. In addition, at the same impact Angle, the damage of the target plate is also affected by the velocity of the projectile body.